Answer:
Kindly refer to below explanation.
Explanation:
Given equation of line:
![(x)/(a)cos\theta+ (y)/(b)sin\theta =1\\OR\\(x)/(a)cos\theta+ (y)/(b)sin\theta-1=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/2dkgwsgiv5yztbhgz0vtmn9uvzzsh1eeee.png)
Given points are:
![(√(a^2-b^2),0), (-√(a^2-b^2),0)](https://img.qammunity.org/2022/formulas/mathematics/high-school/c8mkuudjjd6r9666d7k9szc8w3ke3ugiog.png)
Formula for distance between a point and a line is:
If the point is
and equation of line is
![Ax+By+C = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/6f6lemmhuoo0mhhaxnbgzh82662ziilfex.png)
Then, perpendicular distance between line and points is:
![Distance = (|Am+Bn+C|)/(√(A^2+B^2))](https://img.qammunity.org/2022/formulas/mathematics/high-school/ck273a5f0gu81aug5s05aiiipqnelldy7g.png)
Here,
![A = (x)/(a)cos\theta\\B = (y)/(b)sin\theta\\C = -1](https://img.qammunity.org/2022/formulas/mathematics/high-school/8rc3e98xyvv62f6hlbkk54dbozd5knakti.png)
For the first point:
![m = √(a^2-b^2), n = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/n4dr4jmf7bh6td87ycyu2tcub7xmbowyzv.png)
By the above formula:
and
can be calculated as:
![p* p' =\\\Rightarrow \frac{\sqrt{(cos^2\theta)/(a^2)+(sin^2\theta)/(b^2)}}* \frac{\sqrt{(cos^2\theta)/(a^2)+(sin^2\theta)/(b^2)}}\\\Rightarrow (1-(√(a^2-b^2)* (cos\theta)/(a))^2)/((cos^2\theta)/(a^2)+(sin^2\theta)/(b^2))}](https://img.qammunity.org/2022/formulas/mathematics/high-school/ga6mfknkafod6ohv4tvx60v6ifrg4ctpqg.png)
Formula used:
![(x+y)(x-y) = x^2 - y^2](https://img.qammunity.org/2022/formulas/mathematics/high-school/celwdxudpeb1gv4kv6ya1p9a42iq444oqm.png)
![\Rightarrow ((a^2-a^2cos^2\theta+b^2cos^2\theta)/(a^2))/((b^2cos^2\theta+a^2sin^2\theta)/(a^2b^2))\\\Rightarrow b^2((a^2sin^2\theta+b^2cos^2\theta)/(a^2sin^2\theta+b^2cos^2\theta))\\\Rightarrow b^2](https://img.qammunity.org/2022/formulas/mathematics/high-school/goz5wcot1cigx5fzfhbt5bntia3prva33y.png)
(Using the identity:
)
(Hence provded)